Tapping into past design experiences: knowledge sharing and creation during novice-expert design consultations - Deken,F; Kleinsmann,M; Aurisicchio,M; Lauche,K; Bracewell,RH (Research in Engineering Design, 2012)
Designing is a knowledge-intensive activity. For novice design engineers, an important means of acquiring knowledge is to consult experienced colleagues. We observed novice–expert consultations as part of three engineering projects in a large aerospace company. Seven meetings were analysed in detail regarding the design activity, the content, and the form of interaction. Although the meetings were initiated for the purpose of information seeking , this process amounted to only 8% of the time compared to knowledge creation between novices and experts (47% of meeting time), and contextual information sharing (45% of meeting time). Both experts and novices were found to contribute equally and interactively to the discussion and analysis of solutions. The analysis showed how the processes alternated in the meetings. We identified tentative patterns on how these consultation processes change over the course of the design process phases. The micro-level analysis of the design activities and form of interaction provided a deeper understanding of how the consultation processes are discursively produced by the experts and novices. Finally, implications for design engineering practitioners are derived and suggestions for further research are provided.